Rehydration with sodium enriched coconut water after exercise-induced dehydration - Singh, Rabindarjeet; Sirisinghe, Roland G.; Ismail, Ishak; Nawawi, Mohammad (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2004)
This cross over study assessed the effectiveness of plain water (PW), sports drink (SD), young coconut water (CW) and sodium enriched young coconut water (SCW) on whole body rehydration (R), plasma volume (PV) restoration after exerciseinduced dehydration. Ten healthy male subjects (age range, 19 - 27 years) were exercised at 65% of V02max at an environmental temperature. of 32.06±0.02oe which a relative humidity (RH) of 53.32±0.17% for 90 minutes until 3.08± 0.04% (1.83±0.1 0 kg) of their body weight was loss. After which, the subjects moved to the thermoneutral environment (23.2±0.3°C) and rested for 30 minutes prior to begin the 2-hour R period. During R. Subjects drank either PW, SD, ew or sew in randomized representing 120% of the fluid lost in three boluses representation 50% (915±54 ml), 40% (732± 37m I) and 30% (556±35 ml) of the fluid lost at 0, 30, 60-min respectively. In all the trials subject were somewhat hypohydrated (range 0.32- 0.52 kg) body weight (BW) below euhydrated BW after the 2-h R period. The percent body weight loss that was regained (used as index of percent rehydration) during PW, SD, CW and sew was 58±2o/o, 68±2%, 65±2% and 69±1% respectively with a significant better rehydration with SD and SeW than PW (p<0.05). The rehydration index (RI) for SD and SeW was significantly lower than PW (p<0.01 ). PV was restored similarly to euhydration levels after 2-h of re_hydration with SD, CW and sew but was significantly lower (p<0.05) with PW trials. Cumulative urine output was significantly higher for PW when compare to SD and sew (p<0.05). Serum er were significantly higher with ew and sew trials (p<0.05). Serum Na+, serum K+, serum er and serum and urine osmolality of pW trial were significantly lower (p<O.OS) than SD, CW and SCW at the end of 2-hR period. Plasma glucose concentration were significantly higher when SO, ew· and SeW were ingested during rehydration compared to PW (p<0.01 ). SCW were similar in sweetness with CW and SO but caused less nausea and stomach upset when compares either SD or PW, furthermore sew was easier to consume in large volume. In conclusion~ ingesting SCW was as good as ingesting a commercial sports drink for whole body rehydration after .exercise-induced dehydration but with better fluid tolerance.